ANALISIS TINGKAT PENGETAHUAN DAN KEJADIAN INFEKSI MENULAR SEKSUAL PADA WANITA USIA - Utomo, Bram Mustiko; Inti, sri (Universitas Kadiri, 2024)
Sexually transmitted infections (STIs) are one type of infectious disease that is widespread and has serious risks. East Java ranks ninth as the province with the highest number of HIV/AIDS sufferers, with the highest cases concentrated in Kediri Regency and City. One of the health service centers that is active in handling STIs is the Campurejo Health Center Working Area. In the Campurejo Puskesmas Working Area, as many as 410 cases of STIs were detected in the Campurejo Puskesmas Working Area through a laboratory approach. This study aims to identify the relationship between the level of knowledge and the incidence of STIs in women of childbearing age who visit the STI clinic in the Campurejo Health Center Work Area. Analytical survey method with cross sectional design was used in this study. A total of 56 samples of women of childbearing age were taken using accidental sampling techniques. The results showed that most respondents had a good level of knowledge, which is around 50%. The majority of respondents, 54.6%, did not experience an STI. Bivariate analysis showed that there was a relationship between the level of knowledge and incidence of STIs in women of childbearing age in the Campurejo Health Center Work Area, with a p-value of 0.001 and a correlation coefficient r of 0.450, indicating moderate closeness. Thus, it can be concluded that there is a significant relationship between the level of knowledge and the incidence of STIs in women of childbearing age in the Campurejo Health Center Work Area